Microbiological Quality and Physicochemical Characteristics of Pork Livers Supplied by an Industrial Slaughterhouse - Narcís Feliu-Alsina; Elena Saguer (Polish Journal of Food and Nutrition Sciences)
Pork liver is a by-product generated daily in large quantities due to the high number of pigs slaughtered and its relatively high weight in relation to the carcass weight. However, it is not widely accepted by consumers for direct consumption due to its organoleptic properties. The present work aims to provide information of interest that may be useful for obtaining protein extracts from pork liver with potential as techno-functional ingredients. Specifically, the obtained results indicate that pork liver has a high protein content, with collagen representing only a small protein fraction and being poor in non-protein nitrogenous compounds. In addition, from the solubility profile obtained in the pH range from 4.8 to 8.5, high extraction yields can be expected at alkaline pH. However, and despite the high microbiological quality of pork livers properly collected and processed, their pH, water content and nutritional richness make them highly susceptible to microbiological spoilage.